Cryptic diversity in Astroblepus (Siluriformes: Astroblepidae): Integrative taxonomy reveals evolutionary complexity in the Esmeraldas River Basin, Ecuador - Kevin P. Chugá-Puetate; María Peñaranda-Valla; Daniel Escobar-Camacho; Jonathan Valdiviezo-Rivera; Juan F. Rivadeneira (PLoS ONE, 2026)
Astroblepus is a genus of endemic Andean catfishes with problematic taxonomy because of cryptic diversity, ambiguous historical descriptions, and morphological plasticity. This study applied an integrative taxonomy approach—combining DNA barcoding (COI gene), geometric morphometrics, and traditional morphological characters—to assess the species diversity within the genus Astroblepus in the Esmeraldas River basin (Ecuador), where five species are currently recognized. A total of 395 specimens were analyzed (386 for morphometrics, 33 for genetics), integrating both new and publicly available sequences. The molecular analysis delimited seven evolutionary lineages, exceeding previously known diversity. The validity of A. eigenmanni and A. fissidens was confirmed; a possible synonym between A. mindoensis and A. theresiae was suggested, and A. aff. mindoensis was recovered as their sister group. Within A. cyclopus we identified two cryptic lineages (5.6% divergence), and two new lineages ( Astroblepus sp. and A. aff. mindoensis ) were discovered, characterized by distinct morphometric autapomorphies. Geometric morphometrics revealed four morphological clusters, with significant segregation between A. cyclopus and Astroblepus sp., but overlap within more complex groups. Altitudinal distribution and isolation among sub-basins may be drivers of divergence. These results reveal an underestimated diversity in the basin, highlighting the need for formal taxonomic revisions, sampling in unexplored areas, and urgent conservation strategies considering habitat fragmentation.